PERAN PEMBELAJARAN BERBASIS PROYEK TERHADAP PENINGKATAN PEMAHAMAN KONSEP SISWA KELAS V MATERI SISTEM PENCERNAAN MANUSIA - Vina Amalia Ramadhan; Sunaengsih, Cucun; Sujana, Atep (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low understanding of the concept of grade V students in elementary school is due to the lack of variation in learning delivery methods. Efforts to overcome these problems can be done by applying a project-based learning model to help students build an understanding of concepts through direct experience in completing projects. The purpose of this study is to determine the role of project-based learning models in improving students' understanding of concepts. The method used is a quasi-experiment with a Nonequivalent Control Group Design. The participants in this study were 58 grade V students who were in one of the elementary schools in Kandanghaur District. The research instruments used are observation and tests. Data collection was carried out to see teacher performance and student activities, and concept comprehension tests. The results of the study showed that: (1) the implementation of learning with the project-based learning model obtained very good criteria, both in terms of teacher performance and student activities, (2) there was a difference in the increase in concept understanding from the average N-Gain results in the experimental class and the control class, with the average N-Gain of the experimental class higher than that of the control class. Therefore, it can be concluded that project-based learning plays a positive role in improving concept understanding.